Degradation of poly(3-hydroxybutyrate) and its derivatives: characterization and kinetic behavior - Bonartsev, Anton; Boskhomdzhiev, Arasha; Voinova, Vera; Makhina, Taniana; Myshkina, Vera; Yakovlev, Sergey; Zharkova, Irina; Filatova, Elena; Zernov, Anton; Bagrov, Dmitry; Andreeva, Natalia; Rebrov, Alexander; et al. (Publishing House of Lviv Polytechnic National University, 2012)
We focused on hydrolytic degradation kinetics at 310 and 343 K in phosphate buffer to compare PLA and PHB kinetic profiles. Besides, we revealed the kinetic behavior for copolymer PHBV (20 % of 3-hydroxyvalerate) and the blend PHB-PLA (1:1). The intensity of biopolymer hydrolysis is characterized by total weight lost and the viscosity-averaged molecular weight (MW) decrement. The degradation is enhanced in the series PHBV < PHB < PHB-PLA blend < PLA. Characterization of PHB and PHBV includes MW and crystallinity evolution (X-ray diffraction) as well as AFM analysis of PHB film surfaces before and after aggressive medium exposition. The important impact of MW on the biopolymer hydrolysis is shown. Наведено порівняльні дослідження стосовно гідролітичної деструкції полі-3 гідроксибутирату (РНВ) і поліактиду (PLA) у фосфатному буфері за 310 і 343 К, а також кінетики деструкції кополімеру 3-гідроксибутирату і 3-гідроксивалерату (20%) та суміші PHB-PLA (1:1). Інтенсивність гідролізу характеризувалась втратою загальної маси та пониженням середньов‘язкісної молекулярної маси зразків. Встановлено, що швидкість гідролізу зростає у послідовності PHBV < PHB< суміш PHB-PLA < PLA. З використанням методу РСА визначена еволюція кристалічності та ММ, а із застосуванням методу АСМ показано різницю шороховатості для поверхні РНВ до і після контакту з агресивним середовищем. Показано важливу роль ММ полімеру як чинника, що відповідає за гідролітичну деструкцію біополімерів.
Гідролітична деструкція полі(3-гідроксибутирата) і його похідних: характеристика та кінетична поведінка
Keywords: poly(3-hydroxybutyrate); polylactide; nonenzymatic hydrolysis; crystallinity; weight loss; полі-3-гідроксибутират; поліактид; неферментний гідроліз; кристалічність; втрата маси